Donor–acceptor organic nanostructure based on conjugated polymer for improving visible-light-driven photocatalytic activity towards degradation of dye in aqueous medium. (7th November 2022) - Behere, Ravi Prakash; Laxmi, Raj; Gupta, Neelam; Sharma, Uttam; Das, Santanu; Kuila, Biplab Kumar
Abstract : Hybrid donor–acceptor nanostructures based on P3HT with improved light harvesting properties were employed for organic dye degradation. Abstract : Conjugated-polymer-based donor–acceptor hybrid nanostructures have been the subject of great interest, mainly due to their potential applications in photovoltaic and other electronic and optoelectronic devices. Here, we have demonstrated a different aspect of these hybrid nanostructures toward efficient photocatalysis in an aqueous medium. The hybrid donor–acceptor nanostructures were prepared by assembling a carboxylic acid-functionalized fullerene molecule (phenyl C-61 butyric acid) (PCBA) on the surface of an amine-functionalized regioregular P3HT nanostructure through acid–base interaction. The efficient photoinduced charge separation and charge transfer in the hybrid material were investigated by steady-state and time-resolved photoluminescence and photocurrent measurements. The photocatalytic activity of the hybrid nanostructure in water under visible light irradiation (using a 20 W white LED bulb) was investigated, and it was found to show 82.5% dye degradation efficiency. To facilitate the reusability of the photocatalyst, a membrane-based dip-photocatalyst was developed from this material, and it shows 87.5% dye degradation efficiency and can be reused multiple times without a significant change in degradation efficiency.